Achieving Health for All Primary Health Care in Action - Bishai, David; Schleiff, Meike (Johns Hopkins University Press, 2020)
How did seven low- and middle-income countries, inspired by the landmark Alma-Ata Declaration, dramatically improve citizen health by focusing on primary health care?The Alma-Ata Declaration of 1978 marked a potential turning point in global health, signaling a commitment to primary health care that could have improved the safety of air, food, water, roads, homes, and workplaces in all 180 countries that signed it. Unfortunately, progress in many countries stalled in the 1980s. The declaration was, however, embraced by a number of countries, where its implementation led to substantial improvement in citizen health. Achieving Health for All reveals how, inspired by Alma-Ata, the governments of seven countries executed comprehensive primary health care systems, deploying new cadres of community-based health workers to bring relevant services to ordinary households. Drawing on a set of narrative case studies from Bangladesh, Indonesia, Ethiopia, Nepal, Ghana, Sri Lanka, and Vietnam,the book explains how a primary health care focus succeeded in improving population health. The book also conclusively demonstrates that comprehensive, multisector, community-controlled, and population-level primary health care is a viable strategy that, against the odds, has led to sustainable, scalable good health at lower cost. Bringing together a group of experts to analyze the forty-year legacy of the Alma-Ata Declaration, Achieving Health for All is a fascinating look at the work needed to transform nations from places that make people sick to places where they stay healthy. An inspiring array of lessons learned along the way shows how readers can make policies that support the health of all people.Contributors: Onaopemipo Abiodun, Vinya Ariyaratne, John Koku Awoonor-Williams, Kedar Prasad Baral, Ayaga A. Bawah, Pedro Más Bermejo, Fred N. Binka, David Bishai, Carolina Cardona, Dennis Carlson, Chala Tesfaye Chekagn, Hoang Khanh Chi, Svea Closser, Luc Barrière Constantin, Zufan Abera Damtew, Marlou de Rouw, Nadia Diamond-Smith, Philip Forth, Mignote Solomon Haile, Nguyen Thanh Huong, Taufique Joarder, Alice Kuan, Seblewengel Lemma, Sasmira Matta, Ahmed Moen, Rituu B. Nanda, Frank K. Nyonator, Ferdous Arfina Osman, Claudia Pereira, Henry B. Perry, James F. Phillips, Meike Schleiff, Melissa Sherry, Rita Thapa, Kebede Worku